Cell phone app to optimize irrigation cycles for US crops. (24th April 2020) - Simonet, Daniel; Alnaizy, Raafat
Abstract: Evaporation losses can be reduced by adapting a scheduled irrigation time and having a precise irrigation cycle, but owing to high costs, water optimization tools have thus far been available only to large firms. The study presents all the required steps to develop a smart phone app that can predict the optimal irrigation times for a future 15 days on a sample of 80 crops at any location in the United States. The app uses a soil water balance approach together with data provided by weather sites via application programming interfaces (API). This low‐cost, portable, water irrigation planner only requires the entry of both crop and sprinkler type in order to enhance greatly small farms' and private households' ability to lower their consumption of water and the associated costs. Abstract : Evaporation losses can be reduced by adapting a scheduled irrigation time and finding the right irrigation cycle. The study presents all steps to develop a smart phone app that predicts the optimal irrigation timing for the incoming 15 days on a sample of 80 crops in any location in the United States using a soil water balance approach with data provided by application programming interfaces (API) from weather sites